Synthesis and Properties of a Novel Four-Coordinate 8-Hdroxy-Quinolate-Based Complex - Cheng, Jun; Zhang, Zilong; Wang, Ruiyao; Wang, Hongbo (International journal of molecular sciences, 2025)
Organoboron compounds have attracted significant interest because of their special properties conferring photoluminescence, electroluminescence, and chemiluminescence. However, there are few reported examples of their use in electrochemiluminescence (ECL). This work represents a significant contribution by providing comprehensive evidence that elucidates the critical role of four-coordinate boron coordination in modulating and enhancing ECL properties. By introducing a coordinatively saturated boron center into a designed molecular framework, we achieved a 2.5-fold enhancement in ECL intensity during electrochemical processes. These results address the limited fundamental understanding of ECL behavior pertinent to tetracoordinate boron systems and provide valuable insights into molecular design strategies for developing stable and highly efficient ECL luminophores.